THE MODERN METHODS FOR PREVENTION OF FILLINGS STATIONS NEGATIVE INFLUENCES CAUSED BY EVAPORATION - Черняк, Л.; Радомська, М. (Science-based technologies, 2012)
The independence of fuels losses from evaporation with fuels quality is considered in the article. The research results of efficiency of modern methods for prevention of fillings stations negative influences caused by evaporation are presented.